A novel mode of DnaA–DnaA interaction promotes ADP dissociation for reactivation of replication initiation activity. Issue 21 (19th September 2019) - Sugiyama, Ryo; Kasho, Kazutoshi; Miyoshi, Kenya; Ozaki, Shogo; Kagawa, Wataru; Kurumizaka, Hitoshi; Katayama, Tsutomu
Abstract: ATP-DnaA is temporally increased to initiate replication during the cell cycle. Two chromosomal loci, DARS (DnaA-reactivating sequences) 1 and 2, promote ATP-DnaA production by nucleotide exchange of ADP-DnaA for timely initiation. ADP-DnaA complexes are constructed on DARS1 and DARS2, bearing a cluster of three DnaA-binding sequences (DnaA boxes I−III), promoting ADP dissociation. Although DnaA has an AAA+ domain, which ordinarily directs construction of oligomers in a head-to-tail manner, DnaA boxes I and II are oriented oppositely. In this study, we constructed a structural model of a head-to-head dimer of DnaA AAA+ domains, and analyzed residues residing on the interface of the model dimer. Gln208 was specifically required for DARS -dependent ADP dissociation in vitro, and in vivo analysis yielded consistent results. Additionally, ADP release from DnaA protomers bound to DnaA boxes I and II was dependent on Gln208 of the DnaA protomers, and DnaA box III-bound DnaA did not release ADP nor require Gln208 for ADP dissociation by DARS –DnaA complexes. Based on these and other findings, we propose a model for DARS –DnaA complex dynamics during ADP dissociation, and provide novel insight into the regulatory mechanisms of DnaA and the interaction modes of AAA+ domains.